2004
DOI: 10.1088/0268-1242/19/12/l04
|View full text |Cite
|
Sign up to set email alerts
|

Porosity-induced gain of luminescence in CdSe

Abstract: Porous CdSe layers have been produced by anodic etching of crystalline substrates in a HCl solution. Anodization under in situ UV illumination resulted in the formation of uniformly distributed parallel pores with a diameter of 30 nm, stretching perpendicularly to the initial surface. At the same time, pronounced nonuniformities in the spatial distribution of pores were evidenced in samples subjected to anodic etching in the dark. Gain of luminescence was observed in some porous regions and attributed to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Formation of porous network in a p-type II-VI material, namely, in p-Cd 1−x Zn x Te, was demonstrated by Erne et al 7,8 Recently we succeeded in introducing pores into n-type CdSe, 9 and we observed gain of luminescence in porous regions characterized by strong light scattering. 10 In this article, we show the possibility of introducing arrays of parallel pores with diameters as low as 10-20 nm into highly conductive n-CdSe single crystals. Porosity-induced blueshift of exciton bands in PL spectra of n-CdSe is also reported.…”
Section: Introductionmentioning
confidence: 95%
“…Formation of porous network in a p-type II-VI material, namely, in p-Cd 1−x Zn x Te, was demonstrated by Erne et al 7,8 Recently we succeeded in introducing pores into n-type CdSe, 9 and we observed gain of luminescence in porous regions characterized by strong light scattering. 10 In this article, we show the possibility of introducing arrays of parallel pores with diameters as low as 10-20 nm into highly conductive n-CdSe single crystals. Porosity-induced blueshift of exciton bands in PL spectra of n-CdSe is also reported.…”
Section: Introductionmentioning
confidence: 95%
“…This is due primarily to the significant differences between the properties of porous semiconductors and their bulk counterparts [7], and to the potential new applications that these properties afford. For example, recent studies have reported porosity-induced birefringence in GaP with potential applications in optoelectronics [8,9], luminescence in porous III-V and II-VI semiconductors [10][11][12], the ability of porous III-Vs to support Fröhlich-type surface vibrations [13,14], and a porosity-induced blueshift of photoluminescence in CdSe [15]. There have also been studies of terahertz emission from porous InP [16].…”
Section: Introductionmentioning
confidence: 99%
“…Currentline pores have so far been found in InP and GaP (2, 12 -16), again for a large variety of electrolytes. The classification can be easily extended to pores obtained in II-VI semiconductors (17,18), which closely resemble the currentline pores found in InP, as well as to Si and Ge, where most pore types have always been of the crysto pore type (19 -21), but currentline pore growth can also be obtained (22).…”
Section: Introductionmentioning
confidence: 84%